PERAN PEMBELAJARAN KITAB TA’LIM AL-MUTA’ALIM DALAM PEMBENTUKAN KARAKTER SANTRI DI PP. DARUL ULUM SUGIO - Muhammad Syairozi (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
Character education is an integral part of the pesantren education system, emphasizing the development of students’ morals, ethics, and personal integrity. Ta'līm al-Muta'allim, as one of the classical texts studied in pesantren, teaches essential values such as sincerity in seeking knowledge, respect for teachers, diligence in learning, and proper manners in daily life. This study aims to examine the role of Ta'līm al-Muta'allim instruction in shaping the character of students at Pondok Pesantren Darul Ulum Sugio. A qualitative descriptive method with a case study approach was employed. Data were collected through observation, in-depth interviews with the caregivers, teachers, and students, and documentation of the learning process. The data were analyzed inductively by referring to theories of character education and traditional Islamic learning. The findings reveal that the teaching of Ta'līm al-Muta'allim significantly contributes to character formation. The values presented in the book are not only delivered theoretically but also implemented in daily s tudent life through habitual practice and the exemplary conduct of the teachers. The emergence of character traits such as discipline, humility, respect for teachers, and strong learning motivation indicates the success of internalizing these values. Thus, Ta'līm al-Muta'allim serves as an essential medium for the sustainable and contextual internalization of character values in pesantren education.